Diffusional anisotropy of the human brain assessed with diffusion-weighted MR: relation with normal brain development and aging. - Nomura, Y; Sakuma, H; Takeda, K; Tagami, T; Okuda, Y; Nakagawa, T (American Journal of Neuroradiology, 1994)
PURPOSE To analyze diffusional anisotropy in frontal and occipital white matter of human brain quantitatively as a function of age by using diffusion-weighted MR imaging. METHODS Ten neonates (< 1 month), 13 infants (1-10 months), 9 children (1-11 years), and 16 adults (20-79 years) were examined. After taking axial spin-echo images of the brain, diffusion-sensitive gradients were added parallel or perpendicular to the orientation of nerve fibers. The apparent diffusion coefficient parallel to the nerve fibers (0) and that perpendicular to the fibers (90) were computed. The anisotropic ratio (90/0) was calculated as a function of age. RESULTS Anisotropic ratios of frontal white matter were significantly larger in neonates as compared with infants, children, or adults. The ratios showed rapid decrease until 6 months and thereafter were identical in all subjects. In the occipital lobe, the ratios were also greater in neonates, but the differences from other age groups were not so prominent as in the frontal lobe. Comparing anisotropic ratios between frontal and occipital lobes, a significant difference was observed only in neonates. CONCLUSIONS Diffusion-weighted images demonstrated that the myelination process starts earlier in the occipital lobe than in the frontal lobe. The changes of diffusional anisotropy in white matter are completed within 6 months after birth. Diffusion-weighted imaging provides earlier detection of brain myelination compared with the conventional T1- and T2-weighted images.